The effects of linght emitting diode lighting on growth and development of A. annanesis and A. roxburghii in vitro cultured shoots - Binh Minh, Phan Xuan; Thanh Phuong, Bui Thi; Son, Pham Huong; Hoi, Tran Minh; Phuong Lan, Nguyen Thi; Thao, Vu Thi (Academia Journal of Biology, 2017)
A. annamensis and A. roxburghii belong to Orchidaceae family that has medicinal and ornamental plant value. They are in extinct endangered plants in wild due to the over- collected and loss of the suitable habitats. Using the LED lighting source for culture these species in in vitro condition to optimize the culture conditions, reduction of the production cost, especially electric bill for air-corditionning, lighting. In recent years, the trial applied LED which has the feature of energy saving, small size and a longer operating life, for plant production has started. In this study, LED illumination sources are in four different wavelengths of λ= 430- 470 nm; λ= 470-510 nm; λ= 510-560 nm; λ= 560-600 nm and white fluorescent lamp as control with light intensity photosynthetic photon flux density (PPFD) of 40 µmol/m2/s photon used to study their effects on the growth and development of A. annamensis and A. roxburghii species. After 8 weeks of implementing, the results showed that the LEDs of λ= 470-510 nm were suitable for the growth and development for A. roxburghii shoots while for A. annamensis, λ = 430- 470 nm were most suitable for budding and λ= 470-510 nm for shoot growth. Citation: Phan Xuan Binh Minh, Bui Thi Thanh Phuong, Pham Huong Son, Tran Minh Hoi, Nguyen Thi Phuong Lan, Vu Thi Thao, 2018. The effects of linght emitting diode lighting on growth and development of A. annanesis and A. roxburghii in vitro cultured shoots. Tap chi Sinh hoc, 40(1): x-xx. DOI: 10.15625/0866-7160/v40n1.10636. *Corresponding author: pxbminh@gmail.com Received 23 August 2017, accepted 2 December 2017